HIGHER EDUCATION MINISTER URGES STUDENTS TO CONTINUE BEING COMMUNITY ICONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
GAMBANG, PAHANG, 23 April 2016 – Higher Education Minister, Dato’ Seri Idris Jusoh urges students who have been selected as outstanding personalities to continue being icons and junior ambassadors at all levels of society, from those in schools to those at the international stage.